Digital Consumer Justice as Maqāṣid-Based Ethics: Rethinking Telkomsel’s Data Expiry Policy through Netnography: Keadilan Konsumen Digital sebagai Etika Berbasis Maqāṣid: Memikirkan Kembali Kebijakan Kedaluwarsa Data Telkomsel melalui Netnografi - Taufikin Taufikin (Transformatif, 2026)
The automatic removal of unused data quotas by one of Indonesia's telecommunications service providers has sparked widespread public attention in the digital sphere. This practice is often perceived as undermining consumer justice and rights. However, empirical studies linking digital consumer perceptions to the maqāṣid al-sharīʿah framework remain limited. This study examines public perceptions of Telkomsel's data quota expiration policy through a netnographic approach within an Islamic ethical perspective. Using an interpretive qualitative design, the study analyses 500 YouTube comments, 12 semi-structured interviews, and digital observations. Thematic analysis is grounded in the principles of maqāṣid: justice (ʿadl), protection of property (ḥifẓ al-māl), and public interest (maṣlaḥah). The results show that 36.6% of users view the policy as exploitation, while 25.4% associate it with a violation of digital property rights. Public narratives consistently view quotas as legitimate assets, so their removal is perceived as a unilateral loss. Interviews reinforce the link between injustice, low transparency, and weak consumer protection. This study does not conclude a general ethical crisis, but identifies the emergence of moral criticism rooted in digital experiences. These findings affirm that maqāṣid al-sharīʿah is a relevant evaluative framework for the ethics of digital services. The contribution of this research lies in its effort to empirically link maqāṣid with digital consumption practices, as well as demonstrating that netnography is effective in uncovering ethical dimensions within digital public narratives